(untitled) (Actual Problems of Psychology in Educational Institutions, 2022)
The article is devoted to the development of reflection among primary school pupils, and analyze factors which affect it. Analyzed sources on the subject, diagnosed the developmental level of the reflection in the primary school, graphically depicts the results of diagnostic justified and explained the results obtained on the basis of the processed sources.